SURGICAL METHODS OF TREATMENT OF PATIENTS WITH FORMED PANCREATIC CYSTS - N. V. Merzlikin; N. Yu. Sled; A. Ye. Popov; V. F. Tskhaj; N. A. Brazhnikova; S. V. Shelepov; V. F. Podgornov; V. E. Gyunter; A. N. Kapustinsky; P. S. Bushlanov (Бюллетень сибирской медицины)
Objective: a comparative analysis of the results of the use of different surgical methods of treatment of patients with formed pancreatic cysts.Material and methods. 108 patients with formed pancreatic cysts were treated and analysis of shortand long-term results of their surgical treatment was performed. Patients were divided into three groups depending on the type of surgical intervention: I – external drainage – 44 (40.7%), II – internal drainage –33 (30.6%), III – resection operations – 31 (28.7%).Results and discussions. Marsupialization of cyst by laparotomy incision was performed in patients of I group (n = 44). 18 (40.9%) complications, 9 (20.5%) lethal cases were after operation. Anastomoses of cysts with the small intestine were mostly performed in II group (n = 33) – 21 (63.6%). 7 (21.2%) complications, 1 (3.0%) lethal case were after operation. Distal resections were performed in patients of III group (n = 31) in 16 (51.6%) cases. Duodenum-preserving resections were introduced for treatment of cyst of pancreas head – 12 (38.7%). When performing this type of operations we proposed nikelid titanium stents for the prevention of anastomosis stenosis and preoperative retrograde stenting of the common bile duct for the prevention of damage. 10 (32.3%) complications and no lethal cases were after operation. Immediate results were worse in patients of I group. 47 (43.5%) patients were analyzed in long-term period. The number of recurrences of the disease (13.3%) and long-term mortality (33.3%) prevailed in the group of patients undergoing internal drainage of cysts. Quality of life, level of mental and physical health, that was assessed using SF-36, were higher in group of patients with reactionary treatment.Conclusion. The best immediate and long-term results were noted after resection operations, that enables to recommend their as the most optimal and radical method for treatment of patients with pancreatic cysts. Introducing of duodenum-preserving resections in case of pancreas head cyst improves the quality of patients life.